Stranded! : a mostly true story from Iceland [book with audioplayer] - Ævar Þór Benediktsson, 1984- ([Library Ideas, LLC], 2024)
"This is a story about my grandfather: how he got stranded on a volcanic island, was almost turned into barbecue and found the most important moment in the world."--